2015
DOI: 10.1182/blood-2015-02-628560
|View full text |Cite
|
Sign up to set email alerts
|

CD9, a key actor in the dissemination of lymphoblastic leukemia, modulating CXCR4-mediated migration via RAC1 signaling

Abstract: CD9, a member of the tetraspanin family, has been implicated in hematopoietic and leukemic stem cell homing. We investigated the role of CD9 in the dissemination of B acute lymphoblastic leukemia (B-ALL) cells, by stably downregulating CD9 in REH and NALM6 cells. CD9 expression was associated with higher levels of REH cell adhesion to fibronectin and C-X-C motif chemokine receptor 4 (CXCR4)-mediated migration. Death occurred later in NOD/SCID mice receiving REH cells depleted of CD9 for transplantation than in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 48 publications
(58 reference statements)
4
48
0
Order By: Relevance
“…Celsr1, if reduced, causes otic defects because of loss of apical constrictions due to disturbed actomyosin recruitment to the apical junctional complex (Sai et al, 2014). RNASeq analysis also revealed the induction of cd9b by Notch, a Tetraspanin family member implicated in cell-matrix adhesion and Sdf1 (Cxcl12a) mediated migration (Figure 7L–M’, [Arnaud et al, 2015; Leung et al, 2011]).…”
Section: Resultsmentioning
confidence: 99%
“…Celsr1, if reduced, causes otic defects because of loss of apical constrictions due to disturbed actomyosin recruitment to the apical junctional complex (Sai et al, 2014). RNASeq analysis also revealed the induction of cd9b by Notch, a Tetraspanin family member implicated in cell-matrix adhesion and Sdf1 (Cxcl12a) mediated migration (Figure 7L–M’, [Arnaud et al, 2015; Leung et al, 2011]).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, upon EGF stimulation, it was shown that knockdown of CD81 increases Rac activation. A more recent study identified a correlation between CD9 expression and GTP bound Rac1 expression in acute lymphoblastic leukemia patient samples (Arnaud et al, 2015). Moreover, this group also determined that the C-terminal tail of CD9 is important for regulating Rac1 activation.…”
Section: Tetraspanins and Intracellular Signalingmentioning
confidence: 99%
“…The expression of other proteins might also affect chemokine receptor conformations and thus influence the receptor function. For instance, complexes between CCR5, CXCR4, and CD4 are essential for HIV‐1 infection, and the interaction of CXCR4 with the tetraspanin CD9 modulates CXCL12‐mediated cell migration . The constitutive association of CXCR2 with CCRL2 is essential to fine‐tune CXCR2‐mediated neutrophil recruitment to inflammation sites, and heterodimers between the EBV‐induced receptor 2 (EBI2) and CXCR5 contribute to the plasticity of CXCL13‐mediated B cell responses …”
Section: Chemokine Receptor Dimerization/oligomerization: a Potentialmentioning
confidence: 99%
“…For instance, complexes between CCR5, CXCR4, and CD4 are essential for HIV-1 infection, 50 and the interaction of CXCR4 with the tetraspanin CD9 modulates CXCL12-mediated cell migration. 100 The constitutive association of CXCR2 with CCRL2 is essential to fine-tune CXCR2-mediated neutrophil recruitment to inflammation sites, 70 and heterodimers between the EBV-induced receptor 2 (EBI2) and CXCR5 contribute to the plasticity of CXCL13-mediated B cell responses. 68 Although experimental evidence indicates that the formation of homo-and heterodimers is a general process in the chemokine receptor field, a recent report on class A GPCR members, predicts that this is not always the case, as some receptors exist as monomeric entities.…”
Section: Membrane Lipids Membrane Proteins F I G U R E 1 Chemokine Rementioning
confidence: 99%